A SAW-Based Decision Support System for Selecting Final Project Topics in the Informatics Management Department at STMIK Mulia Darma - Siregar, Kristian; Siagian, Edward Robinson; Tampubolon, Kennedi (Devitara Innovations, 2025)
Selection of Final Project Topics is a crucial stage in the academic process, as it significantly affects the smoothness of project preparation and completion. However, the determination of final project topics often remains subjective and does not systematically consider students’ academic abilities. This study aims to design and develop a Decision Support System for selecting final project topics for students in the Informatics Management Department using the Simple Additive Weighting (SAW) method. The SAW method is employed to evaluate and rank alternative topics based on several criteria, including supporting course grades, student interest, programming skills, system analysis and design capabilities, and the availability of supervising lecturers. The results indicate that the SAW method can provide objective and transparent recommendations for final project topics. Based on the calculation, alternative A4 achieved the highest preference score of 0.962, making it the most recommended final project topic. Therefore, the developed system is expected to assist both students and academic staff in making more effective and structured decisions regarding final project topic selection.